Analisis Implementasi Perencanaan Ppn Dan Ppnbm Pada Pt Astragraphia Xprins Indonesia - Sumarno Manrejo; Dicky Raidaldi Sebayang (LPMP Imperium, 2021)
The purpose of this study was to determine whether the calculation, deposit and reporting of VAT at PT Astragraphia Xprins Indonesia was in accordance with Undang-Undang No. 42 tahun 2009 tentang PPN dan PPnBM, and to see the optimization of value added tax planning at PT Astragraphia Xprins Indonesia. The methodology used is descriptive quantitative and uses secondary data obtained from the company. The results obtained are that the calculation, deposit, and reporting of VAT at PT Astragraphia Xprins is in accordance with the VAT Law, the optimization of tax planning is optimal in terms of tax delays and less than optimal in maximizing the input tax. Suggestions in order to maximize Input Tax by making purchases from partners who have PKP.